2021
DOI: 10.53637/vjii7190
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrapment Evidence: Understanding Its Role in Self-Defence Cases Involving Intimate Partner Violence

Abstract: This article considers what evidence juries need to help them apply the defence of self-defence where a woman claims she has killed an abusive partner to save her own life. Drawing on recent research and cases we argue that expert evidence admitted in these types of cases generally fails to provide evidence about the nature of abuse, the limitations in the systemic safety responses and the structural inequality that abused women routinely face. Evidence of the reality of the woman’s safety options, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Critics have argued that whitestream feminist-inspired law reforms have been complicit (perhaps unintentionally) in the expansion of state power, taking a neoliberal law-and-order approach to tackling crime and offering (individual) therapeutic solutions to "large-scale cultural problems" (Corrigan 2013, 3; see also Bumiller 2008;Nancarrow 2019;Kim 2020;Gruber 2021). However, these calls for tighter laws impact specific community groups, such as Indigenous women who experience violence but fight back (Douglas et al 2020;Douglas et al 2021). For instance, in Australia, Indigenous women are significantly over-represented within prisons across the country, and evidence shows criminal legal interventions designed to protect women can and do misidentify those requiring protection; where an Indigenous woman might fight back, the likelihood of incarceration is much higher, resulting in a ripple affect where Indigenous children are removed from the family and placed into state care (AHRC 2020;Douglas et al 2020;Deslandes et al 2022).…”
Section: Gender-based Violence Feminism and The Criminal Legal Systemmentioning
confidence: 99%
“…Critics have argued that whitestream feminist-inspired law reforms have been complicit (perhaps unintentionally) in the expansion of state power, taking a neoliberal law-and-order approach to tackling crime and offering (individual) therapeutic solutions to "large-scale cultural problems" (Corrigan 2013, 3; see also Bumiller 2008;Nancarrow 2019;Kim 2020;Gruber 2021). However, these calls for tighter laws impact specific community groups, such as Indigenous women who experience violence but fight back (Douglas et al 2020;Douglas et al 2021). For instance, in Australia, Indigenous women are significantly over-represented within prisons across the country, and evidence shows criminal legal interventions designed to protect women can and do misidentify those requiring protection; where an Indigenous woman might fight back, the likelihood of incarceration is much higher, resulting in a ripple affect where Indigenous children are removed from the family and placed into state care (AHRC 2020;Douglas et al 2020;Deslandes et al 2022).…”
Section: Gender-based Violence Feminism and The Criminal Legal Systemmentioning
confidence: 99%
“…Unlike in some other common law jurisdictions, self-defence is not a partial defence to either homicide or assault in England and Wales, nor in Scotland, and the prospect of those who have survived a prolonged course of abusive behaviour using it successfully to avoid responsibility is remote (Bettinson and Wake, forthcoming). The Scottish Law Commission (2021) has observed that its focus on imminent danger ignores the reality that victims are often required to use stealth or surprise to increase the prospects of successful defensive action; and that it fails to recognise the extent to which victims’ assessment of the feasibility of escape is impacted both by their experiences of abuse, as well as by empirically defensible concerns, particularly within some communities, about the reliability and availability of safe alternatives (Douglas et al, 2021; Tolmie et al, 2018). This has been further supported by McPherson's recent analysis (2022), which found that the defence is rarely successful when relied upon by victims of domestic abuse.…”
Section: Coercive Control As a Cause Of Criminalitymentioning
confidence: 99%
“…As Prosecutor 2 put it, ‘there is discussion to be had about whether we widen out what realistically was the exit, when somebody has been told for years that they have nowhere else to go’ but under existing frameworks, ‘it's hard to see what you would do with that … it will always come back down to there was another option available to you and you could have left’. Thus, though the ‘why didn’t she leave’ trope that reduces empathy for survivors of abuse and diminishes their prospects for securing justice and protection from perpetrators may be a less potent feature of contemporary responses to victimisation, participants indicated it remains a feature of defence doctrine in circumstances where the abuse suffered compelled victims towards criminality (Douglas et al, 2021; Tolmie et al, 2018).…”
Section: Coercive Control As a Cause Of Criminalitymentioning
confidence: 99%